2008
DOI: 10.1016/j.econlet.2008.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Technology shocks, structural breaks and the effects on the business cycle

Abstract: This paper contributes to the literature on the role of technology shocks as source of the business cycle in two ways. First, we document that time-series of US productivity and hours are apparently affected by a structural break in the late 60's, which is likely due to a major change in the monetary policy. Second, we show that the importance of demand shocks over the business cycle has sharply increased after the break.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For example, one can use actual economic time series, such as commodity prices, that have been tested for deterministic chaos [14,21,34,68]. Moreover, shocks other than technology shocks can be considered, in view of the on-going debate between two literatures supporting and rejecting the importance of technology shocks for generating business cycles [12,37,54].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one can use actual economic time series, such as commodity prices, that have been tested for deterministic chaos [14,21,34,68]. Moreover, shocks other than technology shocks can be considered, in view of the on-going debate between two literatures supporting and rejecting the importance of technology shocks for generating business cycles [12,37,54].…”
Section: Discussionmentioning
confidence: 99%
“…In more deeply investigating the impacts of technology shocks or supply shocks, it was found that the research papers in the past have revealed some interesting findings; for instance, the introduction of the RBC models has been influential in refocusing attention on supply issues in macroeconomic analyses after the long postwar focus on aggregate demand management in Australia and most other Western economies (Crosby & Otto 1995). Meanwhile, research on the importance of technology shocks on the US business cycle has sharply decreased after a structural break in the late 1960s (Atella et al 2008). At the same time, the RBC model has been further developed for looking at specific issues of shocks in a wide range of areas, e.g., the issue of how representative consumers have to do housework and how shocks in this area can affect the real business cycle (Benhabib et al 1991), the application of the RBC model to the durableand nondurable-goods-producing sectors (Hornstein & Praschnik 1997;Martín-Moreno et al 2014)…”
Section: Literature Reviewmentioning
confidence: 99%